Science no fair! - Krulik, Nancy E.; Burwasser, Amanda Elizabeth (Krulik, Nancy E. Project droid, 2016)
When Logan Applebaum's mother invents a robotic cousin for him, Logan thinks this may give him an edge in the third grade science fair but the Silverspoon twins have other ideas.